PENGARUH REKONDISI MOLD TYPE-2186 TERHADAP PENINGKATAN PRODUKTIVITAS DAN KUALITAS HASIL PRODUKSI - Rusyana, Mohammad Purwa; Rizky Maulana (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2021)
PT. STAR COMGISTIC INDONESIA is a company engaged in household electronics production field that makes 3 types of electronic products namely cooking utensils, electric iron and coffee pot. In the production process must pay attention to the quality at each stage in order to get the best production results optimal. Internship practice shows that the process of making a product that used in the production process must be done carefully and activities according to the existing standard operating procedures (SOP), so that the results of production can be of good quality or the results of production get good results optimal. The internship that was carried out at PT STAR COMGISTIC INDONESIA was on repair molding field. (molding) basically consists of two parts, namely the stationary part of the mold (stationary platen) in which the molten polymer is deposited, and the movable platen on the cover side or ejector side of a injection molding parts.Repair molding is a work in which repairing mold or mold that is damaged or needs maintenance, repair mold is done so that the mold can work properly. After done repair, when the molding is damaged before being repaired then the result production becomes defective or imperfect, for results from before being repaired and after fixing there is already an image in the testing section, for this case it is hoped that the mold can work as before it was damaged so that the product produced from the mold to produce an optimal product.